Development Strategy of Red Seaweed Industry (Rhodophyta) in the Poleang Minapolitan Cluster Bombana Regency - Pratama, Rahmat Tata; Purwadi, Didik; Widodo, Kuncoro Harto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Indonesia is the world’s largest producer of red seaweed, but its utilization as a source of economic growth is still not optimal, as evidenced by the large amount of exports in raw form, insufficient land utilization, and harvest yields that do not meet standards. This study aims to formulate development strategies for the red seaweed industry in the Poleang sub-district of Bombana Regency through the identification of internal and external conditions. Data was collected through observation, interviews, and questionnaires. The analysis used includes descriptive, financial, and SWOT analysis. The results of the study show that the red seaweed industry in Poleang still faces various challenges, such as red seaweed production that does not meet standards, unstable production volumes, seaweed processing plants operating below full capacity, low educational levels among farmers, limited market access and capital resources for farmers, the absence of structured farmer groups, the suboptimal role of financial institutions, climate and weather changes, pests and diseases, and highly volatile seaweed prices. However, there are also significant development opportunities, such as the availability of extensive cultivation areas conducive to seaweed growth, a sufficient labor force, experienced farmers, relatively easy seaweed marketing, simple cultivation techniques, the availability of tissue culture technology and processing industries, profitable cultivation efforts with an RC ratio of 1.94, and the significant potential of the red seaweed market and its processed products both domestically and internationally. Strategies that can be implemented for the development of the red seaweed industry in the Poleang Sub-district cluster of Bombana Regency include optimizing seaweed production through resource optimization, improving productivity and production quality, enhancing the role and functions of institutions, increasing human resource capacity, promoting the use of high-quality seeds, and establishing and strengthening partnership and marketing patterns for seaweed.